Urbanization and sustainability in Asia: case studies of good practice - Roberts , Brian (ed.); Kanaley , Trevor (ed.) (Philippines, 2006)
The book presents case studies of good practice on sustainable urban development from 12 Asian countries: Bangladesh, Cambodia, People's Republic of China, India, Indonesia, Lao People's Democratic Republic, Malaysia, Pakistan, Philippines, Sri Lanka, Thailand, and Viet Nam. It provides insights into current issues, management approaches, and investment types in urban development in Asian setting. It also provides other examples of good practice in sustainable urban development in the context of more advanced economies. It is a useful resource book for city managers, political leaders, and professionals responsible for planning and managing the development of cities.